Regularity Criteria of the Solutions to Axisymmetric Magnetohydrodynamic System (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider Cauchy problem of the axially symmetric Magnetohydrodynamic (MHD) system. By using energy method, weestablish some regularity criteria of the solutions for the axisymmetric solutions of the three dimensional incompressible MHD system.